Indian Ocean challenges a quest for cooperative solutions - Kaushiva, Pradeep; Singh, Abhijit (KW Publishers in association with National Maritime Foundation, 2013)
The Indian Ocean Region (IOR) is of immense strategic significance on the global maritime map - not just on account of its centrality to the current trade and energy flows, but also because of the extreme disparities and inherent volatility of the region. The region faces an array of security challenges, both traditional and non-traditional. These include security of SLOCs, the problem of piracy, the possibility of renewed terrorism at and from the sea and the pervasive smuggling of people, narcotics and arms. The narrative of regional maritime security is also characterized by oscillating economic growth, growing military presence and a rapidly deteriorating ecological balance in the Indian Ocean. A stand-out feature of the IOR is the lack of correspondence between nations on issues concerning 'security'. While using the high seas for trade, transportation of energy, major powers have tended to neglect the impact of the economic activities on the sea itself. In contrast, smaller regional countries and island states with developing economies have, at best, been able to use only those resources of the sea which are vital to their survival. As the challenges rise, the need to factor in and secure effective management of the Indian Ocean has turned into a compelling imperative. While governments and authorities grapple with complex issues trying to forge a coherent maritime policy, there is a growing recognition that unless solutions are found quickly, lives, livelihoods, and in some cases the very future of local populations could be at risk. This book contains a comprehensive overview of perspectives of some of the stakeholders in the Indian Ocean Region. It seeks to identify the key maritime security issues and explores the potential contribution of the stakeholders in meeting these challenges.